2020
DOI: 10.24123/jeb.v1i2.2870
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dynamic Capability in Mediating The Effects of Environmental Dynamism and Managerial Capabilities on Firm Performance: a Preliminary Study

Abstract: Small and Medium Enterprises (SMEs) face many challenges from the coming rapid changes such as technology advancement, competitions, limitations and supports from government regulations, and limitations in terms of capital supply, product knowledge, and company management. Building and maintaining the firm performance of SMEs can be achieved through external factors (environmental dynamism) and internal factors (managerial capabilities). By using the dynamic capabilities as an intervening variable, it is expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…At the same time, this conclusion effectively answers the Only the organizational learning that is consistent with the human resource service enterprises strategy and can be transformed by the dynamic capability of the enterprise, it can improve organizational performance. Thirdly, environmental dynamics and its dimensions have a significantly positive moderation effect between dynamic capability and organizational performance of human resource service enterprises, which is basically consistent with the conclusions of the existing literature (Protogerou et al, 2012;Permana and Ellitan, 2020;Yoshikuni, 2021). However, the more valuable finding of this study is that two dimensions of environmental dynamics (technology environment and market environment) have a positive moderation effect between dynamic capability and organizational performance of human resource service enterprises.…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, this conclusion effectively answers the Only the organizational learning that is consistent with the human resource service enterprises strategy and can be transformed by the dynamic capability of the enterprise, it can improve organizational performance. Thirdly, environmental dynamics and its dimensions have a significantly positive moderation effect between dynamic capability and organizational performance of human resource service enterprises, which is basically consistent with the conclusions of the existing literature (Protogerou et al, 2012;Permana and Ellitan, 2020;Yoshikuni, 2021). However, the more valuable finding of this study is that two dimensions of environmental dynamics (technology environment and market environment) have a positive moderation effect between dynamic capability and organizational performance of human resource service enterprises.…”
Section: Discussionsupporting
confidence: 89%
“…Based on this theory, SMEs may require customers sensing and responding capabilities (Roberts and Grover, 2012). Thus, SMEs may have the ability to immediately detect and return, which are essential to adapt to the current business environment (Permana et al , 2020; Battaglia and Neirotti, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The study shows that environmental changes, including government regulations and changes in consumer demand, affect the performance of MSMEs. A study by Machmud & Sidharta (2016) showed a positive influence of environmental dynamism, while other research such as Permana & Ellitan (2020) found an insignificant influence.…”
Section: Introductionmentioning
confidence: 90%
“…Besides regulations, the impact of changes in consumer nature such as changes in demand, innovation, and technology can affect the performance of MSMEs (Wijbenga & van Witteloostuijn, 2007). Mukherji & Mukherji (2016) stated that environmental dynamism forces MSMEs to be able to survive, find solutions, and be able to prepare for the impact of further environmental changes Permana & Ellitan (2020) and Haleem & Jehangir (2018) argued that environmental dynamism positively affects the performance of MSMEs. This is different from the research by Sandra & Purwanto (2017) that environmental dynamism does not have a significant effect on the performance of MSMEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation